Customer value analysis for product positioning and value-based pricing; creating value for customers and profitable growth for your business - Gale, Bradley T. (Henry Stewart Talks, 2008)
A comprehensive approach to customer value analysis, The objective is to make you aware of the data, techniques, and analysis tools for positioning and pricing your products, Overview of the customer value analysis framework, Case examples that illustrate how product line teams use customer value analysis to resolve competitive marketing strategy issues